Keterampilan Komunikasi Terapeutik Penyuluh Agama di Kota Padang - Rosdialena Rosdialena; Erna Dewita; Fadil Maiseptian; Thaheransyah Thaheransyah; Anna Ayu Herawati (Jurnal Dakwah dan Komunikasi, 2021)
Religious instructors are people who play a role in providing education, guidance, and information to the community. For this reason, the therapeutic skills of extension workers need to be improved continuously, considering that the success of counseling lies in getting the message to the community. The purpose of this study was to measure the level of therapeutic communication based on aspects of the communicator's ability, acceptance of the communicant, the message conveyed, the use of media, and the effect of the interpretation of a message. The type of research conducted is descriptive quantitative. The research subjects of this research were 32 religious instructors in the city of Padang. The data collection tool uses instrument development in the form of a valid and reliable therapeutic communication questionnaire. The data collection technique used quantitative descriptive analysis with the percentage formula. The results of this study indicate that communicators must have the ability to master problems, speak effectively, motivate, look attractive and use appropriate language. Then from the communicant aspect, the extension worker must understand the background and cultural characteristics and the level of need for the communicant for the material presented. The material aspect of the instructor should use structured, monitored, and evaluated material. The use of media in counseling is very supportive of achieving the goals of counseling. Taking into account all these qualifications, the extension worker can avoid misinterpretation of the material presented, so that the target of the extension can be achieved.